2020
DOI: 10.3390/microorganisms8050735
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Pseudomonas aeruginosa Evokes Differential Inflammatory Responses in Human Microglial and Retinal Pigment Epithelial Cells

Abstract: Increasing incidences of multidrug-resistant (MDR) pathogens causing endophthalmitis threaten our ability to treat this condition, and the modulation of inflammatory responses by MDR bacteria is not known. In this study, using human microglia and retinal pigment epithelial (RPE) cells, we compare the inflammatory responses of sensitive (S-PA) and multidrug-resistant (MDR-PA) clinical isolates of Pseudomonas aeruginosa. Infected cells were subjected to qPCR analysis, enzyme-linked immunosorbent assay (ELISA), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Pathway analysis also concurred that the majority of the gene response in our study overlap with genes associated with inflammatory processes in the public database. The cytokine associations uncovered were however expected based on previous studies (16,17). Our previous studies also found similar overexpression of these IL-1b, IL-6, IL-10, and TNF-a cytokines in human microglial cells, retinal pigment epithelial cells, and human vitreous samples.…”
Section: Discussionsupporting
confidence: 81%
“…Pathway analysis also concurred that the majority of the gene response in our study overlap with genes associated with inflammatory processes in the public database. The cytokine associations uncovered were however expected based on previous studies (16,17). Our previous studies also found similar overexpression of these IL-1b, IL-6, IL-10, and TNF-a cytokines in human microglial cells, retinal pigment epithelial cells, and human vitreous samples.…”
Section: Discussionsupporting
confidence: 81%
“…The actions of these bacteria may depend on the structure of the bacterial cell wall components, which are recognized by different TLRs [ 44 , 45 ]. The MDR cell wall components activate distinct TLRs [ 46 , 47 ] that can result in the activation of additional signaling pathways, regulating not only cytokine production [ 43 , 48 ] but, for example, transcription factors that are involved in the regulation of iron metabolism as well, e.g., NRF2 that acts as a transcriptional regulator of both iron exporter ferroportin and the oxidative stress-induced protein heme oxygenase 1, which is also responsible for heme degradation [ 49 , 50 ]. Moreover, NRF2 can modify NFκB activity, which results in decreased cytokine production [ 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB inhibition also increased the formation of autophagosomes, 35 a finding that correlates with our previous in vitro study where the MDR-PA burden was found to be higher than S-PA strain. 9 Interferon-stimulated genes and their association with STAT1 36 were investigated, and STAT1 overexpression was reported in cases of a drug-resistant TB strain. In Bacillus 11 and S. aureus 37 endophthalmitis, it has been shown that phosphorylation of STAT3 influences NF-кB activation and promotes the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Considerable studies have shown that the severity of endophthalmitis is strongly correlated with intraocular inflammation, characterized by the infiltration of neutrophils and the production of inflammatory cytokines. 4 8 An earlier investigation by our group on retinal cells highlighted an exacerbated response of interleukin (IL)-6, IL-1α, IL-8, IL-10, IL-1β, tumor necrosis factor-alpha (TNF-α), and interferon-gamma (IFN-γ) in retinal and microglial cells exposed to MDR strains, 9 suggesting that MDR-PA infections have a more virulent behavior, and this excessive inflammatory response may hamper resolution of the infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation